Determinants of Stunting in Children Under Five in Pontianak City: A Systematic Literature Review - Uliyanti; Adha Panca Wardanu (Muhammadiyah Institute of Technology and Health, West Kalimantan (ITEKES Muhammadiyah Kalimantan Barat), 2025)
Stunting remains a significant public health issue in Pontianak City, with long-term impacts on children's growth and development. This study aims to identify the main determinants of stunting among children under five in Pontianak, determine the dominant contributing factors, and formulate evidence-based policy recommendations for more effective and context-specific interventions. A Systematic Literature Review (SLR) was conducted using articles from Google Scholar and Scopus, published between 2015 and 2024. Literature was retrieved using the keywords